Hypertensive syndromes in pregnancy from the perspective of mobile emergency service nurses - Lopes, Talita Menezes; Chevonik, Isabeli Emily; Prates, Lisie Alende (Disciplinarum Scientia | Saúde, 2025)
Objective: To analyze the perceptions and experiences of nurses regarding the care of hypertensive syndromes in pregnancy within the Emergency Medical Service. Method: This is a qualitative study conducted with eight nurses using semi-structured interviews and thematic content analysis. Results: Most participants reported experience in managing hypertensive syndromes in pregnancy. They mentioned checking vital signs, initiating continuous cardiac monitoring, auscultating fetal heartbeats, establishing peripheral venous access, lateralizing the pregnant woman, and administering medications. However, they pointed out the lack of antihypertensive medications for managing these situations, concerns about care during convulsive crises, and inadequate prenatal care for pregnant women. Final thoughts: The nurses demonstrated knowledge and skills to identify and manage hypertensive syndromes in pregnancy. There is a need to provide the necessary medications for managing these conditions in the service, as well as to emphasize the importance of prenatal care and blood pressure control.